he Effect of Various Plant Fluor and Egg Fluor to Internal Temperature, pH, Taste and Crispy Level of Fried Chicken - Ahmad Bayu Ariawan; Harapin Hafid (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
Fried chicken is the food product which is made from chicken meat by using deep frying method. This product processed with milk marinate during 8 hours of storage, then it powdered to distribute the chicken meat until it was tawny and crispy by floor as the support ingredient. This study aims to analyze using the plant floor and egg floor as seasoned floor to internal temperature, pH and organoleptic characteristic of fried chicken. This study used Completely Random Design (CRD) including 4 treatments: Seasoned floor (P0), sticky rice floor (P1), sago floor (P2) and egg floor (P3). The measurement parameters used are internal temperature, pH and organoleptic characteristic. This study showed that using plants floor and egg floor had not significance to internal temperature and pH (p>0.05), but had significance to taste and crispy level (p<0.05). The plant fluor (sticky rice and sago) has good primacy to quality of fried chicken.